Wireless sensor networks and energy efficiency : protocols, routing, and management - Zaman, Noor, 1972-; Ragab, Khaled; Abdullah, Azween Bin, 1961- (Hershey PA : Information Science Reference)
"This book focuses on wireless sensor networks and their operation, covering topics including routing, energy efficiency and management"--